Measures of Central Obesity are Better than BMI for Understanding Cardiometabolic Risk - Wareham, Nick (MD Conference Express, 2011)
Studying abdominal obesity provides important clues on the pathophysiology and natural history of diabetes and cardiovascular disease. This article provides recent insights on abdominal obesity and cardiometabolic risk from the European Prospective Investigation into Cancer [EPIC] study.